Kombinasi Koagulasi-Filtrasi Berbahan Lokal Kepulauan dalam Mengurangi Kadar Kekeruhan Pada Air Sumur Gali Di Pulau Barrang Caddi, Kota Makassar - Muhammad Aidil Fitrah; Agus Bintara Birawida; Ain Khaer; Blego Sedionoto; Budirman Budirman (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Small islands often face challenges in providing clean water, including the poor quality of dug wells on Barrang Caddi Island. This study aims to evaluate the effectiveness of coagulation using moringa seeds and filtration using pumice and mangrove charcoal in reducing turbidity and improving water quality. The study design is a quasi-experimental study using a one-group pretest-posttest approach. Samples were purposively selected from one dug well with the highest TDS value that is actively used. The treatment was conducted in three replicates to ensure consistency and reliability of the results. The coagulation process used Moringa oleifera at a dose of 350 mg/l, while filtration used pumice and activated charcoal media with a thickness of 60 cm. Effectiveness was calculated based on the difference in turbidity levels before and after treatment and analyzed using the Kruskal-Wallis test and post hoc analysis. The results showed significant differences in all methods applied (p = 0.016). Moringa seed coagulation reduced turbidity by 26.85%, pumice filtration by 68.72%, activated carbon filtration by 79.96%, and the coagulation-filtration combination by 74.80%. Activated carbon filtration demonstrated the highest adsorption capacity. This study concluded that the combination of coagulation and filtration is a practical and applicable solution for addressing clean water issues in coastal and island regions. Keywords: Coagulation; Filtration; Moringa Seeds; Pumice; Activated Charcoal from Mangrove Wood